Electrochemical Corey–Winter reaction. Reduction of thiocarbonates in aqueous methanol media and application to the synthesis of a naturally occurring α-pyrone - López-López, Ernesto Emmanuel; Pérez-Bautista, José Alvano; Sartillo-Piscil, Fernando; Frontana-Uribe, Bernardo A. (Beilstein Journal of Organic Chemistry, 2018)
An electrochemical version of the Corey–Winter reaction was developed giving excellent results in aqueous methanol media (MeOH/H2O (80:20) with AcOH/AcONa buffer 0.5 M as supporting electrolyte), using a reticulated vitreous carbon as cathode in a divided cell. The electrochemical version is much more environmentally friendly than the classical reaction, where a large excess of trialkyl phosphite as reducing agent and high temperatures are required. Thus, cathodic reduction at room temperature of two cyclic thiocarbonates (−1.2 to −1.4 V vs Ag/AgCl) afforded the corresponding alkenes, trans-6-(pent-1-enyl)-α-pyrone and trans-6-(pent-1,4-dienyl)-α-pyrone, which are naturally occurring metabolites isolated from Trichoderma viride and Penicillium, in high chemical yield and with excellent stereo selectivity.
Keywords: Corey–Winter reaction; electrosynthesis; 6-pentyl-2H-pyran-2-ones; reduction; thiocarbonates

(untitled) - Corey, E. J.; Winter, R. A. E. (J. Am. Chem. Soc., 1963)

(untitled) - Corey, E. J.; Carey, F. A.; Winter, R. A. E. (J. Am. Chem. Soc., 1965)

Name Reactions for Functional Group Transformations - Mergott, D. J. (Corey-Winter olefin synthesis, 2007)

(untitled) - Corey, E. J.; Hopkins, B. (Tetrahedron Lett., 1982)

(untitled) - Ramirez, E.; Sánchez, M.; Meza-León, R. L.; Quintero, L.; Sartillo-Piscil, F. (Tetrahedron Lett., 2010)

(untitled) - Pérez-Bautista, J. A.; Meza-León, R. L.; Cruz-Gregorio, S.; Quintero, L.; Sartillo-Piscil, F. (Tetrahedron Lett., 2016)

(untitled) - Moss, M. O.; Jackson, R. M.; Rogers, D. (Phytochemistry, 1975)

(untitled) - Sperry, J. B.; Wright, D. L. (Chem. Soc. Rev., 2006)

(untitled) - Yoshida, J.-i.; Kataoka, K.; Horcajada, R.; Nagaki, A. (Chem. Rev., 2008)

(untitled) - Waldvogel, S. R.; Janza, B. (Angew. Chem., Int. Ed., 2014)

(untitled) - Horn, E. J.; Rosen, B. R.; Baran, P. S. (ACS Cent. Sci., 2016)

(untitled) - Yan, M.; Kawamata, Y.; Baran, P. S. (Chem. Rev., 2017)

(untitled) - Chiba, K.; Okada, Y. (Curr. Opin. Electrochem., 2017)

(untitled) - Rosen, B. R.; Werner, E. W.; O’Brien, A. G.; Baran, P. S. (J. Am. Chem. Soc., 2014)

(untitled) - Anderson, L. A.; Redden, A.; Moeller, K. D. (Green Chem., 2011)

(untitled) - Francke, R.; Little, R. D. (Chem. Soc. Rev., 2014)

(untitled) - Broese, T.; Francke, R. (Org. Lett., 2016)

(untitled) - Nguyen, B. H.; Perkins, R. J.; Smith, J. A.; Moeller, K. D. (Beilstein J. Org. Chem., 2015)

(untitled) - Little, D.; Moeller, K. D. (Electrochem. Soc. Interface, 2002)

(untitled) - Tang, F.; Chen, C.; Moeller, K. D. (Synthesis, 2007)

(untitled) - Moeller, K. D. (Synlett, 2009)

(untitled) - Yoshida, J.-i.; Shimizu, A.; Ashikari, Y.; Morofuji, T.; Hayashi, R.; Nokami, T.; Nagaki, A. (Bull. Chem. Soc. Jpn., 2015)

(untitled) - Shimizu, A.; Hayashi, R.; Ashikari, Y.; Nokami, T.; Yoshida, J.-i. (Beilstein J. Org. Chem., 2015)

(untitled) - Zhao, H.-B.; Hou, Z.-W.; Liu, Z.-J.; Zhou, Z.-F.; Song, J.; Xu, H.-C. (Angew. Chem., Int. Ed., 2017)

(untitled) - Steckhan, E.; Arns, T.; Heineman, W. R.; Hilt, G.; Hoormann, D.; Jörissen, J.; Kröner, L.; Lewall, B.; Pütter, H. (Chemosphere, 2001)

(untitled) - Schäfer, H. J. (C. R. Chim., 2011)

(untitled) - Frontana-Uribe, B. A.; Little, R. D.; Ibanez, J. G.; Palma, A.; Vasquez-Medrano, R. (Green Chem., 2010)

(untitled) - Mihelcic, J.; Moeller, K. D. (J. Am. Chem. Soc., 2004)

(untitled) - Yin, B.; Inagi, S.; Fuchigami, T. (Beilstein J. Org. Chem., 2015)

(untitled) - Palma, A.; Cárdenas, J.; Frontana-Uribe, B. A. (Green Chem., 2009)

(untitled) - Frontana-Uribe, B. A.; Moinet, C. (Tetrahedron, 1998)

(untitled) - Frontana-Uribe, B. A.; Moinet, C.; Toupet, L. (Eur. J. Org. Chem., 1999)

(untitled) - Klemm, L. H.; Olson, D. R. (J. Org. Chem., 1973)

(untitled) - Crich, D.; Beckwith, A. L. J.; Chen, C.; Yao, Q.; Davinson, I. G. E.; Longmore, R. W.; Anaya de Parrodi, C.; Quintero-Cortés, L.; Sandoval-Ramirez, J. (J. Am. Chem. Soc., 1995)

(untitled) - Sánchez-Eleuterio, A.; Sandoval-Lira, J.; Garcia-Sánchez, J.; Monterrosas-Pérez, L.; Hernández-Pérez, J. M.; Quintero, L.; Sartillo-Piscil, F. (J. Org. Chem., 2013)

(untitled) - Barton, D. H. R.; Hartwig, W.; Motherwell, W. B. (J. Chem. Soc., Chem. Commun., 1982)